Interventions for reducing blood pressure in prehypertension: A meta-analysis - Li, Wenjing; Liu, Hao; Wang, Xinai; Liu, Jingying; Xiao, Hongling; Wang, Chenqi; Wu, Yaxuan (Frontiers in Public Health, 2023)
Background: We aimed to address which interventions best control blood pressure (BP) and delay disease progression in prehypertension and to give recommendations for the best option following a quality rating. Methods: A Bayesian network meta-analysis was used to assess the effect of the intervention on BP reduction, delaying hypertension progression and final outcome, with subgroup analyses for time and ethnicity. Recommendations for interventions were finally based on cumulative ranking probabilities and CINeMA. Results: From 22,559 relevant articles, 101 eligible randomised controlled trial articles (20,176 prehypertensive subjects) were included and 30 pharmacological and non-pharmacological interventions were evaluated. Moderate-quality evidence demonstrated that angiotensin II receptor blockers, aerobic exercise (AE), and Dietary Approaches to Stop Hypertension (DASH) lowered systolic blood pressure (SBP). For lowering diastolic blood pressure (DBP), AE combined with resistance exercise (RE) or AE alone provided high quality evidence, with calcium channel blockers, lifestyle modification (LSM) combined with drug providing moderate quality evidence. LSM produced the best BP lowering effect at 12 months and beyond of intervention. In Asians, TCD bubble was moderate quality evidence for lowering SBP and RE may have had a BP lowering effect in Caucasians. No recommendation can be given for delaying the progression of hypertension and reducing mortality outcomes because of low to very low quality of evidence. Conclusion: AE combined RE are preferentially recommended for BP control in prehypertension, followed by DASH. Long-term BP control is preferred to LSM. Asians and Caucasians add TCD bubble and RE to this list as potentially effective interventions.